2012
DOI: 10.3367/ufnr.0182.201210e.1047
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular vibrational redistribution: from high-resolution spectra to real-time dynamics

Abstract: 1 ³ÕÓÑÅÑ ÅÑÄÑÓâ, Ä ÔÑÑÕÄÇÕÔÕÄËË Ô ÐÑÏÇÐÍÎÂÕÖÓÑÌ ØËÏËÚÇÔÍËØ ÄÇÜÇÔÕÄ ì àÕÑ ÃÖÕËÐ-1 Ë ÒÇÐÕËÐ-1 (1-butyne, 1-pentyne), ÅAEÇ ÙË×Ó ÖÍÂÊÞÄÂÇÕ Ð ÒÑÎÑÉÇÐËÇ ÕÓÑÌÐÑÌ ÔÄâÊË C C. £ AEÂÎßÐÇÌÛÇÏ AEÎâ àÕËØ ÏÑÎÇÍÖÎ ÏÞ ÚÂÜÇ ËÔÒÑÎßÊÖÇÏ âÄÐÖá ÔÕÓÖÍÕÖÓÐÖá ×ÑÓÏÖÎÖ, ÐÑ ËÐÑÅAE AEÎâ ÍÓÂÕÍÑÔÕË ì ËØ ÖÒÓÑÜÈÐÐÑÇ ÐÂËÏÇÐÑÄÂÐËÇ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 260 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…[3] This result is not surprising because it is well known that IVR times are strongly dependent on excitation energies. [5] We stress again that τ 0 and the IVR time do not coincide, but to some extent these quantities are correlated to each other. The main difference between nitrobenzene and naphthoquinone derivatives is the incident electron energy ε at which we evaluate the anion lifetimes and the corresponding EA a (τ a ) values.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…[3] This result is not surprising because it is well known that IVR times are strongly dependent on excitation energies. [5] We stress again that τ 0 and the IVR time do not coincide, but to some extent these quantities are correlated to each other. The main difference between nitrobenzene and naphthoquinone derivatives is the incident electron energy ε at which we evaluate the anion lifetimes and the corresponding EA a (τ a ) values.…”
mentioning
confidence: 84%
“…[4] τ 0 may also be compared with the typical intramolecular vibrational energy redistribution (IVR) time in high-resolution IR spectroscopy of cooled molecular beams and real-time studies of IVR dynamics, although the IVR time is strongly dependent on energy and molecular structure. [5] It has been shown that the S 2 (1B u + ) excited state of the β-carotene molecule relaxes in 160 fs to S 1 (2A g À ) and then undergoes two distinct stages of IVR, with 200 and 450 fs time constants. [6] The typical timescale in Rice-Ramsperger-Kassel-Markus (RRKM) theory is also about 100 fs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent monomolecular reactions (dissociation, isomerization) are statistical in nature. The fast redistribution of energy from the pumped mode to other vibrations of the molecule (intramolecular vibrational redistribution, IVR (see review articles: [109][110][111][112]) also limits the possibility of selective vibrational multiphoton excitation of the selected modes of polyatomic molecules above the randomization threshold. Research on intramolecular relaxation, i.e.…”
mentioning
confidence: 99%
“…In this continuing quest a fundamental and formidable phenomenon that needs to be reckoned with is that of intramolecular vibrational energy redistribution (IVR) (1)(2)(3)(4)(5). Although models of reaction rates like the Rice-Ramsperger-Kassel-Marcus (RRKM) theory and transition state theory (TST) continue to be of immense value in terms of their conceptual elegance and ease of application, the deviations from these paradigms due to incomplete IVR can lead to a deeper understanding of reaction dynamics and control (6,7).…”
mentioning
confidence: 99%